Ex Vivo Human Placental Perfusion Model for Analysis of Fetal Circulation in the Chorionic Plate. (18th February 2016) - Gordon, Zoya; Glaubach, Lilia; Elad, David; Zaretsky, Uri; Jaffa, Ariel J.
Abstract : Objectives: The purpose of this study was to develop an ex vivo placental perfusion model to assess changes in the umbilical artery systolic‐to‐diastolic (S/D) ratio due to progressive occlusion of the placental arterial system. Methods: Ex vivo human placentas were connected to a computerized pulse duplicator mimicking pulsatile flow from the fetal heart. Doppler sonographic measurements were conducted on the umbilical and chorionic arteries of 25 mature placentas. Simulation of placental occlusion was performed by progressive ligature of the chorionic arteries, including one umbilical artery. The correlation between the umbilical artery S/D ratio and the severity of simulated placental occlusion was analyzed. Results: The normal mean S/D ratio ± SD decreased gradually along the chorionic plate from 2.66 ± 0.47 at the cord insertion to 1.90 ± 0.59 in generation IV of the chorionic vessels. The Doppler index initially increased slowly with simulated placental occlusion. Only when all 4 generations were occluded was the umbilical artery S/D ratio elevated. Complete occlusion of one umbilical artery resulted in a 39% increase in the umbilical artery S/D ratio. Conclusions: This unique model combining Doppler sonography with perfusion of an ex vivo placenta can be used for a better understudying of pathologic placental blood flow circulation.